Seismic damage of gravity abutment in liquefied ground. Issue 1 (7th December 2018) - Wang, Haitao; Shen, Jiayu; Gao, Da
Abstract : Purpose: Abutment damage in liquefied ground is an important form of seismic damage of bridge structure. This paper aims to further research the effect of beam restriction on seismic damage mode of abutment in liquefied ground. Design/methodology/approach: Based on the investigation of the seismic damage of Shengli Bridge in Tangshan earthquake, the finite element software dynamic effective stress analysis for ground (UWLC) is used to simulate the seismic damage of Shengli Bridge, and the results were compared with the actual seismic damage results. Then, the influences of the horizontal binding force of the beam, the liquefaction layer thickness, the top weight of the abutment, the peak acceleration, the liquefaction layer buried depth and the type of the foundation soil on the abutment seismic damage model are studied. Findings: The results show that numerical simulation results are consistent with the actual seismic damage, and it is feasible to use UWLC software to simulate seismic damage. The results show that the seismic failure mode of the gravity abutment in liquefied ground is slip–rotation coupling type, not single slip type or rotation type. The large deformation of abutment bottom layer, horizontal binding force of the beam and post-stage soil pressure are the main reasons for abutment rotation or even destruction. Research limitations/implications: A series of basic assumptions are used in the calculation process in this paper. The gravity abutment is defined as the elastic body and neglects its local deformation. The soil layer is a homogeneous isotropic. The consolidation process and the drainage boundary problem are not considered in the calculation process. Therefore, the paper may have some limitations. Originality/value: To further research the seismic damage mode and influencing factors of abutment in liquefied ground, in this paper, based on the investigation of the seismic damage of Shengli Bridge in Tangshan earthquake, the finite element software UWLC is used to simulate the seismic damage of Shengli Bridge, and the results were compared with the actual seismic damage results. The seismic damage mode and influencing factors of gravity abutment in liquefied ground have been studied.